To framework, or not to framework? Reflections from co-design of a digital supportive care platform for patients with brain tumours and their carers - Mahima Kalla; Kit Huckvale; Ashleigh Bradford; Verena Schadewaldt; Sarah C. E. Bray; Ann Borda; Kara Burns; Heidi McAlpine; Joseph Thomas; Daniel Capurro; Richard De Abreu Lourenco; Sarah Cain; et al. (Digital Health)
While it is widely acknowledged that co-design will enhance project outcomes, including for digital health innovation, the definition and application of co-design remain heterogenous. Efforts to systematise co-design as a meaningful and rigorous methodology, have been made over the past decades using co-design frameworks. However, we find that co-design frameworks present challenges when operational contexts are complex, and research problems nebulous, as is often the case in digital health research and development initiatives. Here, we present our experience of co-designing a self-guided supportive care digital health platform for Australians affected by brain tumours, called ‘Brain Tumours Online’. The Brain Tumours Online platform seeks to mitigate unmet supportive care needs of patients and their carers through a three-pronged approach: a repository of evidence-based information, an online peer support community, and a directory of validated digital therapeutic tools. Our co-design approach for this platform was influenced by three key contextual considerations: a) disparate operating models and competing priorities of partner organisations; b) patient population-specific needs; and c) the need to practice epistemic flexibility and adaptation to evolving project needs. Instead of following a standardised co-design framework, we adopted methodological pluralism, with a bespoke multi-modal co-design approach. This approach allowed us to combine strengths of various stakeholders and mitigate organisational barriers of working across sectors, characteristic of digital health initiatives in healthcare. Layperson summary In the realm of digital health innovation, co-design is recognized as crucial for achieving successful outcomes. Co-design refers to a participatory method whereby stakeholders, such as patients and carers, collaborate with design professionals to design solutions for problems. In the past, applying co-design methods has proved to be challenging, as there exist many different interpretations and contexts. In this paper, we reflect on the complexities we experienced when co-designing a supportive care digital health platform for Australians affected by brain tumours. Challenges encountered during this study included differing organizational priorities among partners, specific needs of patients, and the necessity for adaptable methods that respond to evolving project demands. To address these challenges, we used a variety of methods instead of adhering to a single systematized co-design framework. Our experience highlights how incorporating adaptability and engaging with different stakeholders in flexible ways can lead to better outcomes for digital health projects. By sharing what we have learned, we hope to encourage more flexible and collaborative approaches in digital health innovation, which can make treatments and tools more effective and useful for everyone involved.